PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) UNTUK PENINGKATAN KEMAMPUAN BERPIKIR KREATIF DAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN TEMATIK DI KELAS 3 SDN CIPOCOK JAYA 2 - Alda Liga Vela; Zerri Rahman Hakim; Lili Fajrudin; Euis Fidyana (Journal of Professional Elementary Education, 2023)
This research is a Classroom Action Research (PTK) which aims to improve creative thinking skills and learning outcomes of third grade students at SD Negeri Cipocok Jaya 2. Problems found in the learning process include less active students, monotonous learning, most students tend not to ask questions and some students' ability to think creatively is still not visible. To overcome these problems the researcher conducted classroom action research related to the application of the Problem Based Learning (PBL) learning model to improve creative thinking skills and learning outcomes of class III students at SD Negeri Cipocok Jaya 2 in Theme 7 Sub-themes 2 and 3 semester II. This study consisted of two cycles, each cycle consisting of three meetings each consisting of action planning, action implementation, observation, and reflection and evaluation. The data in this study were obtained from observation, document study, and tests. Improving students' creative thinking skills can show that pre-cycle the percentage of students' creative thinking abilities was 71.06% then increased in cycle I with a percentage of 86.84% and increased again in cycle II with a percentage of 89.47%. While student learning outcomes in the pre-cycle with a percentage of 55.26% increased in cycle I with a percentage of 78.94% and in cycle II again increased with a percentage of 86.84%. So, the application of the Problem Based Learning (PBL) model is proven to improve creative thinking skills and learning outcomes for Class III students of SD Negeri Cipocok Jaya 2 in Theme 7, Sub-themes 2 and 3